New insights on the fossil mammals from Casal de’Pazzi (Rome) - Pandolfi, Luca; Martino, Roberta; Palombo, Maria Rita (Journal of Mediterranean Earth Sciences, 2023)
The mammal fauna from Casal de’Pazzi (Rome) has been listed in several papers during the past decades, but a detailed taxonomic study has never been published. In this paper, the specimens retrieved or still embedded in sediments from the musealized area of the Casal de’Pazzi site are described and compared for the first time. The morphological and morphometric analyses allow the detection of the following taxa: Palaeoloxodon antiquus, Canis cf. lupus, Crocuta cf. spelaea, Equus sp., Stephanorhinus kirchbergensis, Hippopotamus cf. amphibius, Sus scrofa, Cervus elaphus, Dama dama, and Bos primigenius. The studied remains, although comprising a small sample compared to those collected in situ during excavations, represent an important record in the context of the Middle Pleistocene faunal assemblages of the Roman Basin.